2015 IEEE International Conference on Robotics and Automation (ICRA) 2015
DOI: 10.1109/icra.2015.7139623
|View full text |Cite
|
Sign up to set email alerts
|

Robust trajectory design for object throwing based on sensitivity for model uncertainties

Abstract: Throwing an object by a powered robot system is of great importance in unmanned environments. In this paper, we consider the problem of throwing a point-mass object to minimize uncertainty in the object's landing position, given uncertainty in (1) the robot's initial configuration and (2) friction at the joints. Our analysis assumes that the robot's throw is executed using open-loop torque commands, and it relies on the linearized sensitivities of (a) landing location with respect to release state, (b) release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…• optimizing the robot trajectory in order to reduce the discontinuity (in the rigid-body model) of cable tensions at the launch instant, which may cause oscillations after launch; • studying tension fluctuations that are triggered, in the elastic model, even before the launch (see Figure 6); • analyzing the sensitivity of the final position of the launched object to errors in the actual launch position and velocity with respect to their ideal values, similarly to the works presented in [11,27]; • considering the effect of air drag; the trajectory of a point-mass object in free-flight through a viscous medium is described by differential equations that generally do not allow closed-form solutions, but some authors [29] propose tractable models that approximate the real solution; • experimentally validating our results by tests on a prototype (currently under development).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• optimizing the robot trajectory in order to reduce the discontinuity (in the rigid-body model) of cable tensions at the launch instant, which may cause oscillations after launch; • studying tension fluctuations that are triggered, in the elastic model, even before the launch (see Figure 6); • analyzing the sensitivity of the final position of the launched object to errors in the actual launch position and velocity with respect to their ideal values, similarly to the works presented in [11,27]; • considering the effect of air drag; the trajectory of a point-mass object in free-flight through a viscous medium is described by differential equations that generally do not allow closed-form solutions, but some authors [29] propose tractable models that approximate the real solution; • experimentally validating our results by tests on a prototype (currently under development).…”
Section: Discussionmentioning
confidence: 99%
“…The trajectory planning of the launched mass requires some simplifying assumptions. Most authors [13][14][15][16][17]19,21,[25][26][27][31][32][33][34][36][37][38][39] consider a simplified model where, during the free-flight phase, the only force acting is gravity; under these assumptions, it can be readily shown that the center of mass of the launched object will move along a parabolic arc in a vertical plane. Considering the effect of air drag leads to a more realistic model; however, the dynamic problem including the air-drag model does not have a closed-form solution.…”
Section: Launch Trajectory Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Throw specific objects vs. throw generic objects: The majority of previous approaches to throwing were limited to throwing one specific object type ( [1]: a wooden block; [2]- [4], [6], [13], [18]- [20]: a ball; [5]: a square plastic plate; [15], [17]: heavy boxes). In contrast, two recent approaches targeted throwing of a variety of generic objects [8], [9], We review these next.…”
Section: Specific Objectmentioning
confidence: 99%
“…On the other hand, Okada (Okada et al, 2015) has proposed sensitivity analysis for a dynamical system, and designed a robust throwing motion with small sensitivity. Moreover, their method has been experimentally evaluated (Okada et al, 2018).…”
Section: Introductionmentioning
confidence: 99%